The Impact of Supply Chain Integration on SMES Sustainability Performance: The Mediating Role of Agile Capabilities and Lean Outsourcing - Erwin Juliyanto; Gede Ariadi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
Traditional markets play a crucial role in developing local products, with a focus on sustainable performance. Most of the traders in the traditional market come from small and medium enterprises (SMEs), which tend to struggle with increasing sustainability performance practices, often facing obstacles to supply chain integration as a catalyst. Thus, we examined the interaction effects between supply chain integration and sustainability performance, through agile capabilities and lean outsourcing as mediators from the perspective of Dynamic Capability Theory. This study uses partial least squares-structural equation modelling to explore structural relationships. The sample in this study consisted of 139 SME traders who had stalls in the Pancasari traditional market. The empirical results showed that the indirect positive statistical effect of agile capabilities and lean outsourcing on the linkage between supply chain integration and sustainability performance. Practically, encouraging SME traders to proactively build collaborative relationships with suppliers, distributors, and customers that share information on demand forecasts and enable rapid response to change through agile capabilities. Additionally, lean operations enable traders to systematically identify and eliminate waste by mapping work processes to pinpoint inefficiencies within the business.